Evolution of satellite communications: Integration of ETSI BSM and DVB‐RCS for future satellite terminals. (1st April 2015) - de Cola, Tomaso; Marchese, Mario; Mongelli, Maurizio
Summary: The main added value of the European Telecommunications Standards Institute broadband satellite multimedia (ETSI BSM) architecture is the definition of the Satellite Independent‐Service Access Point (SI‐SAP) protocol interface, which formally separates Satellite Dependent (SD) from SI layers, thus enabling the implementation of powerful vertical QoS mapping strategies. On the other hand, DVB‐S2/RCS satellite standard is considered the driving technology to integrate satellite with terrestrial infrastructure and provide up‐to‐date services. This paper focuses on the integration of ETSI BSM architecture and DVB‐RCS technology, by analysing the adaptations needed on real DVB‐RCS terminals to be interoperable with the SI‐SAP interface. To this end, the detailed design of an underlying architecture taking into account required adaptations and new functionalities is proposed. The possible further evolutions of the BSM specification are also highlighted, showing the potential for the development of future devices integrating both DVB‐RCS and ETSI BSM architectures also in view of the recent upgrade to the DVB‐RCS2 standard. The paper also validates the SI‐SAP QoS functionalities and proves the performance benefits in terms of QoS and quality of experience of Web‐browsing by means of a satellite emulator developed fors this aim. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The paper surveys the essentials of the ETSI BSM architecture, with particular attention on the SI‐SAP interface and the services it provides in terms of QoS, address resolution, multicast and data traffic. The paper shows how the SI‐SAP interface can be integrated into DVB‐S2/RCS2 satellite systems from architecture and real implementation view point. The analysis is corroborated by performance assessment obtained with an ad hoc network emulator, which was used to demonstrate the key functionalities of the integrated satellite architecture.